Análise dos parâmetros respiratórios de crianças no pós-operatório de cirurgia cardíaca com atelectasia e derrame pleural - Alves, Adriane Muller Nakato (2013)
The analysis of respiratory mechanics allows to check lung function and changes for complication or injury of the lung. The analysis of arterial blood gases is important for adjustments in ventilatory parameters, enabling to check complications related to ventilation. The main objective of this study is to associate physical and functional parameters of the lung in children aged 0 to 1 year old, under mechanical ventilation postoperative cardiac surgery through the analysis of ventilatory parameters, respiratory mechanics with conventional radiographic procedure. In total, 46 children were analyzed in this age, but only those who had respiratory pattern and representative radiographs of the atelectasis and pleural effusion were selected. From 30 selected children, 10 had atelectasis and 8 had pleural effusion (PE). The data were analyzed before and after the onset of pulmonary complication. The data of the children without complication was originally used to check the possibility of analysis of respiratory mechanics through controlled cycles and their relationship to the data of arterial blood gases. Data were collected through the respiratory mechanics monitor and graph Inter ® GMX and program Wintracer and analysis of lung area by radiography through AutoCAD ® 2012. The analysis of the controlled waves of the respiratory cycles in assisted controlled mode of the newborn showed that the potential of hydrogen ionic (pH) does not change relatively to the value expected normal. All parameters of respiratory mechanics showed alterations between states with and without pulmonary complication. Among the groups with atelectasis there was statistically significant reduction in parameters tidal volume (VT), lung area (LA) and partial pressure of arterial oxygen (PaO2) and increase in respiratory frequency (RF) and Time in invasive mechanical ventilation (IMV). For the PE group there was a significant decrease in LA and significant increase in time at IMV. The compliance values were below normal for age and the resistance above normal values in all groups. The results of the Spearman coefficient (ρ) showed statistical significance between the LA with the parameters for the pulmonary atelectasis group in Raw parameters (ρ = -0.648 and P = 0.043) and the group with PE in Cst ( ρ = 0.786 and P = 0.021). The results of this study have shown that the analysis of respiratory mechanics can be performed daily in these children and be used frequently. It allows important information of lung function and can be analyzed in assisted controlled mode without the need of sedating the child. The physical structure correlated with the functionality of the lung, although not all parameters have been well correlated. Also, there is a correlation between the structure of lung and its function.